Virtual, augmented and mixed reality : industrial and everyday life applications : 12th International Conference, VAMR 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: industrial and everyday life applications : 12th International Conference, VAMR 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part II (2020) - Unknown
No abstract available